Effectiveness of shrinkage-reducing admixture in reducing autogenous shrinkage stress of ultra-high-performance fiber-reinforced concrete. (November 2015) - Yoo, Doo-Yeol; Banthia, Nemkumar; Yoon, Young-Soo
Abstract: This study describes the effect of shrinkage-reducing admixture (SRA) on free and restrained autogenous shrinkage behaviors of ultra-high-performance fiber-reinforced concrete (UHPFRC). To investigate the cracking potential, tensile strength development was experimentally obtained and predicted on the basis of the degree of hydration model. Three different SRA to cement weight ratios of 0, 1, and 2% and three different reinforcement ratios of 1.3, 2.9, and 8.0% were considered. A higher SRA content contributed to a slightly higher tensile strength and a lower autogenous shrinkage. In addition, a higher SRA content and a lower reinforcement ratio resulted in better restrained autogenous shrinkage behaviors, such as lower autogenous shrinkage stress and cracking potential. Therefore, it can be concluded that the use of SRA or a lower reinforcement ratio is favorable for improving the restrained shrinkage behaviors of UHPFRC.